Abrogation of oncogenic k-ras function by andrographolide derivatives via in silico, in vitro, and in vivo approaches - Quah, Shun Ying (2021)
The rat sarcoma (Ras) proteins are small guanosine triphosphatases (GTPases) that act as molecular switches in major signalling pathways involved in cell proliferation, differentiation, and survival, such as mitogenactivated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) cascades. Ras exists in three isoforms – K-Ras, H-Ras, and N-Ras. Approximately 30% of all human cancers harbour Ras mutations, with the most frequently mutated isoform being K-Ras, which exclusively appears in pancreatic ductal adenocarcinoma (PDAC). Mutated K-Ras proteins are constitutively active with the GTPase activity being compromised. Oncogenic K-Ras is currently a valuable oncology target and its inhibition represents an important therapeutic strategy. Recent in silico study has revealed a direct binding of andrographolide (AGP) and its benzylidene derivatives, SRJ09 and SRJ23, to K-Ras oncoprotein, which abrogated its function and downstream MAPK signalling. The present study aims to investigate the potential of AGP derivatives as anti-Ras therapeutics through in silico, in vitro, and in vivo approaches. The anticancer potential of SRJ09 and SRJ23 has been welldemonstrated in the human colon (HCT-116) and prostate (PC-3) cancer cells, respectively. These two cell lines have been made resistant to the compounds previously and were used in the present study to examine the altered gene profile in relation to the expression of regulatory genes involved in the compounds’ anticancer activity using microarray analysis. Regulatory genes associated with autophagy and apoptotic processes, such as ATG12 and HMOX1, as well as MAPK and PI3K pathways, such as FGF19 and SPRY2 that play major roles in promoting cell growth and survival, were found to be altered. New benzylidene derivatives have been previously synthesised using SRJ09 and SRJ23 as parent compounds, yielding SRS compounds. In the present investigation, the most druggable binding pocket on K-Ras mutants namely p2 was revealed through in silico simulations. SRJ23 and SRS157 were found to bind via intermolecular hydrogen bonding to this pocket. The anti-PDAC activity of selected AGP derivatives (SRJ23, SRJ09, SRS07, and SRS157) and their mechanisms of action were elucidated in vitro. SRJ23 and SRS157 were shown to perform differently particularly in terms of activity on Erk, a crucial signalling protein in the K-Ras-associated MAPK cascade. Its activation was unanticipatedly enhanced by SRJ23 and significantly suppressed by SRS157 upon 24-h treatment of the compounds. SRS07 presented as a superior anti-PDAC agent by promoting oxidative stress, possibly through enhancement of Akt activation in the K-Ras-mediated PI3K pathway. A simple pharmacokinetic study performed in BALB/c mice at a single dose of 100 mg/kg SRJ23 revealed that the compound achieved a maximum plasma concentration of 18.8 μM after 30 min of administration, with long halflife (4.28 h) and mean residence time (6.30 h). Subsequent in vivo antitumour study reported that 100 mg/kg SRS157 delayed the doubling of tumour growth in the PDAC-xenograft nude mouse model more effectively than SRJ23 at the same dose. In conclusion, the outcomes of the present study provide a strong indication of the potential of AGP derivatives, which specifically target the oncogenic K-Ras and abrogate its function, as promising clinical antipancreatic cancer candidates.